Rare Pediatric Pulmonary Diseases: Insights from a Survey of Pediatric Pulmonologists in German-Speaking Countries - Carlens, Julia; Micic, Srdjan; Schwerk, Nicolaus; Griese, Matthias; Moeller, Alexander; Seidl, Elias (Klinische Pädiatrie, 2025)
Rare pediatric pulmonary diseases, such as childhood interstitial lung disease and congenital thoracic malformations, pose diagnostic and therapeutic challenges due to their low prevalence and clinical heterogeneity. In contrast to cystic fibrosis and primary ciliary dyskinesia, which are supported by dedicated care networks, many other rare pediatric pulmonary diseases lack structured management pathways. This study aimed to assess pediatric pulmonologists’ clinical exposure, confidence, and educational needs related to rare pediatric pulmonary diseases. A web-based survey was distributed to all 914 members of the German Society for Pediatric Pulmonology. The questionnaire evaluated clinical experience, diagnostic confidence, and preferences for educational contents and formats. Responses were analyzed using descriptive statistics and group comparisons. Among 209 respondents (22.9% response rate), clinical exposure was low (median: 3 patients/y; interquartile range: 1–5), with 22.5% treating none. Only 36.7% of respondents felt confident in suspecting a rare pediatric pulmonary disease, 22.0% in diagnosis, and 13.3% in treatment. Educational interest was high (68.8%), particularly in clinical presentation (70.7%), treatment (69.8%), and imaging (59.0%). Clinicians with<10 years of experience reported greater interest in clinical presentation than those with≥10 years (84.5% vs. 57.3%, p=0.0002). Workshops, webinars, and online discussions were the most preferred learning formats. Despite limited exposure and low reported confidence, pediatric pulmonologists express strong interest in further education on rare pediatric pulmonary diseases. Tailored, accessible educational strategies are essential to improve awareness, diagnosis, and care for children with rare pulmonary conditions.
Keywords: seltene Lungenerkrankung; Fragebogen; kongenitale thorakale Malformation; diffus parenchymatöse Lungenerkrankung; Pädiatrie